A comparison of the efficacy of varenicline and bupropion and an evaluation of the effect of the medications in the context of the smoking cessation programme. Issue 1 (December 2017) - Benli, Ali; Erturhan, Selman; Oruc, Muhammet; Kalpakci, Pinar; Sunay, Didem; Demirel, Yeltekin
Abstract Background Within the context of the support program for smoking cessation, initiated by the Turkish Ministry of Health in 2011, those who present at 'smoking cessation' centres and are found to be suitable for pharmacological treatment are given varenicline and bupropion free of charge. As the smoking cessation programme is centralized, the selection of the medication is made randomly to provide a fixed distribution rate. The aim of this study was to evaluate the efficacy of both varenicline and bupropion in smoking cessation and to evaluate the effect of the smoking cessation programme. Methods A total of 405 individuals who met the study criteria were included in the study. Smoking habits and degree of dependence were determined in all the participants with the Fagerstrom test for nicotine dependence (FTND) and bupropion or varenicline therapy was initiated in those who were eligible. Patients were followed up at 15 days then at 1, 2, 3, 6 and 12 months after smoking cessation. A level of CO < 5 ppm and 'point prevalence abstinence' were used as the criteria of success for smoking cessation and this evaluation showed the non-smoking status in the previous 7 days. Results The mean age of the participants was 35.19 ± 7.73 years and 82.8% (n  = 334) were male. Of the participants, 60.2% (n  = 244) were given varenicline and 39.8% (n  = 161) bupropion. The mean FTND and package/year was not significantly different between the groups. The rates of success in the 1st and 2nd weeks, and 1st, 3rd and 6th months were significantly higher in the varenicline group than in the bupropion group (p  < 0.05). At the end of one year, the rate of smoking cessation was determined as 13.9% (n  = 34) in the varenicline group and 6.2% (n  = 10) in the bupropion gruop. The difference was statistically significant (p  = 0.015). At the end of 1 year when the previous 7 days smoking status was evaluated with the 'point prevalence abstinence' measurement as the success criteria, success rates were 20.5% with varenicline and 18.6% with bupropion and the difference was not significant (p  = 0.646). The individuals who used the medications for 45 days or longer were more successful in smoking cessation (p  < 0.001). The most common reasons given for discontinuing the medication were the side-effects (31.5%). No significant difference was determined between the groups in respect of the side-effects observed. Conclusions Although the rates of smoking cessation in all the other control points were higher with varenicline than with bupropion, no significant difference was found between the success rates of varenicline and bupropion used in smoking cessation based on the last 7 days at the end of one year. Those who used the medications for 45 days or longer were more successful in smoking cessation.